Assessing the Effectiveness of Mobile Learning Devices in Tertiary Institutions: The Experience of Undergraduates in a Nigerian Private University - Odukoya, Jonathan Adedayo; Adekeye, Olajide; Okunlola, Sola (International Journal of Interactive Mobile Technologies (iJIM), 2017)
Over the years, technology appears to be making life easier and better. However, in some instances, it appears technology is counterproductive. Mobile learning devices, as the name suggests, have been developed to facilitate learning on the move. The questions are: Are these devices truly facilitating learning? If they are truly facilitating learning, are they facilitating learning positively or negatively? To answer these questions, the survey research design was adopted on a sample of 215 randomly selected students. In the process, questionnaire and focused group discussion guideline were used to collect relevant data. Data analysis was both qualitative and quantitative. Some of the core findings from this investigation were that majority of the respondents, and by extension the target population, were barely using the tablets and free internet browsing megabytes [10Gb monthly] given to all students for the intended purpose of learning. Some were pre-occupied with downloading videos, films and music while some spend endless hours playing computer games or chatting on social networks with the attendant consequence of poor learning, dwindling academic performance and productivity. Relevant recommendations to redress this unwholesome trend were proffered